Standardizing the classification of skin tears: validity and reliability testing of the International Skin Tear Advisory Panel Classification System in 44 countries. (1st July 2020) - Van Tiggelen, H.; LeBlanc, K.; Campbell, K.; Woo, K.; Baranoski, S.; Chang, Y.Y.; Dunk, A.M.; Gloeckner, M.; Hevia, H.; Holloway, S.; Idensohn, P.; Karadağ, A.; et al.
Summary: Background: Skin tears are acute wounds that are frequently misdiagnosed and under‐reported. A standardized and globally adopted skin tear classification system with supporting evidence for diagnostic validity and reliability is required to allow assessment and reporting in a consistent way. Objectives: To measure the validity and reliability of the International Skin Tear Advisory Panel (ISTAP) Classification System internationally. Methods: A multicountry study was set up to validate the content of the ISTAP Classification System through expert consultation in a two‐round Delphi procedure involving 17 experts from 11 countries. An online survey including 24 skin tear photographs was conducted in a convenience sample of 1601 healthcare professionals from 44 countries to measure diagnostic accuracy, agreement, inter‐rater reliability and intrarater reliability of the instrument. Results: A definition for the concept of a 'skin flap' in the area of skin tears was developed and added to the initial ISTAP Classification System consisting of three skin tear types. The overall agreement with the reference standard was 0·79 [95% confidence interval (CI) 0·79–0·80] and sensitivity ranged from 0·74 (95% CI 0·73–0·75) to 0·88 (95% CI 0·87–0·88). The inter‐rater reliability was 0·57 (95% CI 0·57–0·57). The Cohen's Kappa measuring intrarater reliability was 0·74 (95% CI 0·73–0·75). Conclusions: The ISTAP Classification System is supported by evidence for validity and reliability. The ISTAP Classification System should be used for systematic assessment and reporting of skin tears in clinical practice and research globally. What's already known about this topic? Skin tears are common acute wounds that are misdiagnosed and under‐reported too often. A skin tear classification system is needed to standardize documentation and description for clinical practice, audit and research. What does this study add? The International Skin Tear Advisory Panel Classification System was psychometrically tested in 1601 healthcare professionals from 44 countries. Diagnostic accuracy was high when differentiating between type 1, 2 and 3 skin tears using a set of validated photographs. Linked Comment:  Vitoriano. Br J Dermatol 2020; 183 :13–14 .